2021
DOI: 10.1186/s12885-021-07927-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of rehabilitation pathways in women with breast cancer in the first 12 months of the disease: a retrospective study

Abstract: Background Breast cancer (BC) presents important physical and psychological challenges that should be appropriately addressed through continuous, integrated and individualized rehabilitation programs after treatment. In this study, we aimed to collect more information on the rehabilitation patterns and utilization of healthcare services by women with BC. Methods We retrospectively analyzed data from two archives of the Lazio Regional Health System … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…BCa patients may experience significant psychological, psychosocial and physical challenges that can be appropriately addressed by rehabilitation during and after therapy which can decrease the side effects and facilitate the process of recovery [84]. There is need for BCa patients to receive adequate rehabilitation especially during the first 12 months after diagnosis and both inpatient and outpatient rehabilitative care should include motor rehabilitation, cognitive or psychological therapy and pathology-related interventions [85]. There are studies that have reported that aerobic exercise subsequent to BCa surgery can increase shoulder joint range of motion, improved pulmonary function, better quality of life (QoL) and pain relief [86,87].…”
Section: Telerehabilitation Covid-19 and Breast Cancermentioning
confidence: 99%
“…BCa patients may experience significant psychological, psychosocial and physical challenges that can be appropriately addressed by rehabilitation during and after therapy which can decrease the side effects and facilitate the process of recovery [84]. There is need for BCa patients to receive adequate rehabilitation especially during the first 12 months after diagnosis and both inpatient and outpatient rehabilitative care should include motor rehabilitation, cognitive or psychological therapy and pathology-related interventions [85]. There are studies that have reported that aerobic exercise subsequent to BCa surgery can increase shoulder joint range of motion, improved pulmonary function, better quality of life (QoL) and pain relief [86,87].…”
Section: Telerehabilitation Covid-19 and Breast Cancermentioning
confidence: 99%
“…BCa patients may experience significant psychological, psychosocial and physical challenges that can be appropriately addressed by rehabilitation during and after therapy which can decrease the side effects and facilitate the process of recovery [81]. There is need for BCa patients to receive adequate rehabilitation especially during the first twelve months after diagnosis and both inpatient and outpatient rehabilitative care should include motor rehabilitation, cognitive or psychological therapy and pathology-related interventions [82]. There are studies that have reported that aerobic exercise subsequent to BCa surgery can increase shoulder joint range of motion, improved pulmonary function, better quality of life (QoL) and pain relief [83,84].…”
Section: Telerehabilitation Covid-19 and Breast Cancermentioning
confidence: 99%
“…Identifying patients at risk of arm morbidity and providing rehabilitation programs can help survivors throughout their journey to recovery [14]. Therefore, the importance of understanding the risk factors and their effect on morbidity, including health behaviors, the type of oncological treatments including type of surgery, and even the patient's emotional state, increases [15].…”
Section: Introductionmentioning
confidence: 99%